Pijat Akupresur untuk Menurunkan Nyeri pada Lansia dengan Gout Arthritis: Studi Kasus: Acupressure Massage for Pain Reduction in Older Adults with Gout Arthritis: A Case Study - Aprilio, Rachmad; Natasha, Brylianti Medica; Budiman, Muhammad Alghifari; Aprilyadi, Nadi (Chakra Brahmanda Lentera Institute, 2026)
Gout arthritis is an inflammatory joint disease caused by the deposition of monosodium urate crystals, characterized by pain, swelling, and limited joint movement. The pain experienced by patients may reduce their quality of life; therefore, effective management through both pharmacological and non-pharmacological approaches is needed. Acupressure therapy is one of the complementary interventions that can be used to relieve pain. This case study aimed to describe the implementation of acupressure therapy in reducing pain intensity among older adults diagnosed with gout arthritis. This study employed a descriptive case study design involving two older adults diagnosed with gout arthritis. The observed variable was pain intensity before and after the implementation of acupressure therapy. Data were collected using a family nursing assessment format and the Numeric Rating Scale (NRS) to measure pain intensity. Acupressure therapy was administered three times within one week by applying pressure to the KI3 (Taixi) and SP6 (Sanyinjiao) acupoints. Following three sessions of acupressure therapy, both participants experienced a reduction in pain intensity. The pain score of both participants decreased from a score of 6 (moderate pain) to a score of 3 (mild pain). These findings indicate that acupressure therapy contributed to pain reduction and may serve as an effective complementary nursing intervention for older adults with gout arthritis. The implementation of acupressure therapy at the KI3 (Taixi) and SP6 (Sanyinjiao) acupoints was effective in reducing pain intensity among older adults with gout arthritis. Therefore, acupressure therapy can be considered a complementary non-pharmacological nursing intervention to help manage pain in patients with gout arthritis.